Teachers' deliberation on communicative potentials in classrooms when students express racism. Issue 1 (2nd January 2020) - Arneback, Emma; Englund, Tomas
ABSTRACT: This article focuses on teachers' deliberation on communicative potentials in classrooms when students express racism. More precisely, we are interested in what aspects are of importance when teachers reflect, deliberate on, and decide how to act. To elaborate on these aspects we turn to John Dewey's work on intra- and interpersonal deliberation, and to interviews with 27 Swedish high school teachers. In the results, we present three aspects of importance in teachers' reflections: (1) individual students' potential for growth, (2) classroom climate and violations, and (3) teachers' knowledge and experiences. Based on the results, we argue that if teachers' experiences of these aspects are positive, they are more open to a deliberative communicative approach. From our perspective, the limits of deliberation in classrooms need more attention, since they expose crucial tensions in teachers' work and dealings with issues related to power, politics, and morality in schools.